Upaya Meningkatkan Kepedulian Masyarakat Dalam Pembayaran Pajak Bumi dan Bangunan - Elda Ermawati; Hanida Hanida; Muhammad Nasir; Novita Ariani; Salaras Wita; Siti Nabila Safarina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Land and Building Tax (PBB) is one of the revenues for local governments which is very important for funding infrastructure development, health services, education and other public services. PBB has a very significant role in community compliance and awareness in paying PBB in various regions is still said to be low. This is usually caused by several factors such as a lack of socialization, minimal transparency in the use of PBB funds, and low public awareness of the use of PBB payments, which is the main cause of low taxpayer compliance. The aim of this research is to identify strategies to be implemented to increase public awareness and compliance in paying PBB. This research uses a qualitative approach using observation and documentation methods. This research shows that the results show that by having regular outreach campaigns or outreach, utilizing information technology in the payment process, as well as developing a compensation and public quality improvement system funded by PPB, it will be an effective step to increase public compliance in paying taxes. Apart from that, involving several community leaders and non-governmental organizations in tax awareness outreach or education is also able to strengthen community responsibility and participation in regional development. By implementing existing strategies, it is hoped that we will be able to overcome problems such as low awareness and low community compliance in PBB payments, which will then be able to support the sustainability of the ability to achieve goals in implementing regional development programs